Developing and implementing a new methodology to test the affordability of currently popular weight loss diet meal plans and healthy eating principles - Ella L. Bracci; Rachel Milte; Jennifer B. Keogh; Karen J. Murphy (BMC, 2022)
Abstract Background Weight loss diets continue to rise in popularity; however, the associated costs are seldom reported. Certain weight loss diets may be unaffordable and differ from their traditional nutrition composition to include non-conventional premium products. In contrast, healthy eating principles such as the Australian Guide to Healthy Eating (AGHE) and the Mediterranean Diet (MedDiet) place an emphasis on fresh produce and staple foods but are sometimes thought to be unaffordable. A new methodology was piloted to assess the cost of weight loss diets using seven meal plans. Methods Seven meal plans were analysed to quantify the absolute grams required of all ingredients across seven days and multiplied by the cost of the ingredient per gram to determine the total cost of each ingredient based on unit size and price. The weekly grocery shopping cost was determined through summation of all ingredients and their entire unit size to compare weekly costs. Results Weekly meal plans (absolute grams) cost between $93-193AUD. The AGHE meal plan was the least expensive and 8 Weeks to Wow was the most expensive. Weekly grocery shopping of entire units cost between $345-$625AUD, over $100AUD greater than the spending of an average Australian ($237AUD/week). Conclusions The financial feasibility for long-term sustainment of weight loss diets may be questionable for groups including low-income earners and low socioeconomic status. Further, when dietary patterns are adapted for weight loss, or followed by consumers, deviations from foundational principles tend to occur which may influence overall cost.